Impact of sugar and acid adulteration on safety of honey produced by Apis mellifera Linnaeus and Heterotrigona itama cockerell bees - Fakhlaei, Rafieh (2021)
Honey is the natural sweet substance produced by honeybees from the nectar of plants or excretions of plant-sucking insects on the living parts of plants. Honey, has been used for anti-ageing, enhancing libido and immune system, treatment of bronchial phlegm, and relieving sore throat, cough, and cold. Honey possesses various pharmacological properties and health benefits such as anti-inflammatory, antioxidant, anti-cancer activities. Thus, honey is prone to be adulterated through inappropriate labelling and fake mixing with cheap and low-quality honey, sugars, and other substances. Consumption of adulterated honey may cause several health modifications such as weight gain, diabetes, liver, and kidney dysfunction. A standard protocol to develop honey toxicity in zebrafish is still uncertain due to unpredictable factors. So, in this study, an optimized protocol was developed to investigate honey toxicity and metabolite fingerprinting in zebrafish, embryo and adult. Therefore, the aims of this study were: 1) to determine the lethal concentration (LC50) of adulterated honey using zebrafish embryo, 2) to elucidate toxicology of selected adulterated honey based on lethal dose (LD50) using adult zebrafish, 3) to determine the effects of adulterated honey on histological changes of zebrafish and, 4) to screen the metabolites profile of adulterated honey by using zebrafish blood serum. Hence, two types of honey were collected from the acacia environment (Heterotrigona itama and Apis mellifera). Pure H.itama was adulterated by different types of sugar such as light corn sugar, cane sugar, inverted sugar, and palm sugar (in the proportion of 1-3% (w/w) from the total volume). On the other hand, acid adulterants such as acetic acid, citric acid, and tamarind were added to A.mellifera honey in the proportion of 3, 5, and 7% (w/w). The LC50 was determined by the toxicological assessment of honey samples on zebrafish embryos in different exposure concentrations in 24, 48, 72, and 96 hours’ post-fertilization (hpf). Pure A.mellifera and H.itama honey represent the LC50 of 31.10±1.63 (mg/ml) and 34.40±1.84 (mg/ml) at 96 hpf, respectively. Acetic acid has the lowest LC50 (4.98±0.06 mg/ml) among acid adulterants while inverted sugar represents the lowest LC50 (5.03±0.92 mg/ml) among sugar adulterants. The highest concentration (7% for acids and 3% for sugar) of adulterants were used to study the toxicology of adulterated honey using adult zebrafish in terms of acute, prolong-acute, and sub-acute test. The results of the LD50 from the sub-acute toxicity test of pure A.mellifera and H.itama honey were 2.18±0.45 (mg/ml) and 2.33±0.04 (mg/ml), respectively. The histological studies of internal organs show a lesion in the liver, kidney, and spleen of adulterated treated-honey groups compared to the control group that can be extrapolated to the human tissue alteration. Furthermore, the LC-MS/MS method was used for metabolite profiling from the zebrafish’s blood serum which were force-fed by pure and adulterated A.mellifera and H.itama honey. Chemometrics analysis was performed by correlating the metabolites detected with toxicity of pure and adulterated honey samples using orthogonal partial least square discriminant analysis (OPLS-DA) model. These results revealed six endogenous metabolites in both pure and adulterated honey treated group as follow: (1) Xanthotoxol, (2) S-Cysteinosuccinic acid, (3) 2,3-Diphosphoglyceric acid, (4) Cysteinyl-Tyrosine, (5) 16-Oxoandrostenediol, and (6) 3,5-Dicaffeoyl-4-succinoylquinic acid. The zebrafish toxicity test could be a standard method for assessing the potential toxicity of honey toxicology. According to this study, all studied adulterants have health disadvantages toward human health based on their LC50, LD50 value and internal organ toxicology. According to a significant (p ≤ 0.05) increase of mortality rate (%) of zebrafish- embryo and adult- in both sugar and acid adulterated honey, it proved that food additives, may not be beneficial toward human health all the time. The kidney, liver and spleen are the main organs that fail due to the consumption of adulterated honey by in vivo histological examination. This study also successfully identified endogenous metabolites that were responsible for the toxic impact of adulterated honey using LC-MS/MS based metabolomics integrated with chemometrics analysis. Considering all approaches, these results might be a promising candidate for early diagnostic biomarkers that can prevent the developing of metabolic diseases such as diabetes (type 1 and 2). The information gained from this research will permit an evaluation of the potential risk associated with the consumption of adulterated as compared to pure honey.